Juvenile Delinquency and Factor Affecting - Salunkhe, Tejashree; Manjushri S. Bagul (International Journal of Scientific Research in Science and Technology, 2024)
The phrase "juvenile delinquency" refers to criminal activities committed by non-major offenders, or those under the age of 18, and study has been done to examine the current state of juvenile delinquency. This study intends to investigate the delinquents' educational history as well as their familial background. background and their financial situation, which has an impact on young people or leads to juvenile criminality. The current study concludes that the primary factors contributing to the rise in this delinquent tendency are low family income, family background (nuclear, joint, or homeless), and a lack of parental supervision over their children. Those in the age bracket commit the majority of the crimes.
Keywords: Juvenile; Delinquency; Prevention; Community; Family background; educational background; justice